Severe respiratory failure secondary to Varicella zoster pneumonia - (:unkn) unknown (My University, 2010)
Varicella, çocukluk çağı bulaşıcı hastalıklarındandır. Erişkinde görüldüğünde ciddi komplikasyonlarla seyredebilir. Pnömoni, erişkin çağında varicella infeksiyonunun en ciddi komplikasyonlarından biridir ve yüksek mortalite ile seyreder. Yoğun bakımda izlem gereken ve mekanik ventilator ihtiyacı gösteren vakalarda mortalite %50 olarak bildirilmektedir. Sunulan olgu pnömoni tanısı ile yoğun bakım ünitesinde takip edilirken varicella pnömonisi tespit edilmiştir. Bu olgudaki tanı ve tedavi yaklaşımımız literatürdeki bilgilerle beraber sunulmuştur. Klin Den Ar Derg 2010; 1(2): 113-116

Varicella is one of the most contagious diseases of childhood. Whenever varicella is seen in adults, it can cause serious complications. Pneumonia is one of the most serious complications of varicella during adulthood and it has a high mortality rate. Cases of varicella pneumonia which need mechanical ventilation in intensive care unit, have %50 of mortality rate. This report presents a patient who was diagnosed as varicella pneumonia in our intensive care unit. Our treatment and diagnostic approach is presented together with actual literature. J Clin Exp Invest 2010; 1(2): 113-116
Varicella zoster pnömonisine bağlı gelişen ciddi solunum yetmezliği
Keywords: Cerrahi